2011
DOI: 10.2337/db11-0291
|View full text |Cite
|
Sign up to set email alerts
|

Total Soluble and Endogenous Secretory Receptor for Advanced Glycation End Products as Predictive Biomarkers of Coronary Heart Disease Risk in Patients With Type 2 Diabetes

Abstract: OBJECTIVECirculating levels of soluble receptor for advanced glycation end products (sRAGE) likely comprise both a secreted isoform (esRAGE) and wild-type RAGE cleaved from the cell membrane. Both sRAGE and esRAGE have been proposed as biomarkers of cardiovascular disease (CVD), but prospective data are limited. We examined the relationship of sRAGE and esRAGE to incident coronary heart disease (CHD) and stroke in type 2 diabetic patients followed for 3.9 years in a trial of atorvastatin: the Collaborative Ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
140
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 27 publications
17
140
2
1
Order By: Relevance
“…Thus, it is likely that IL-6 will not add a great amount of information to a model in the presence of CRP. sRAGE has not been studied in many prospective studies of type 2 diabetes; we previously showed that higher levels were associated with an increased risk of CHD but little difference in stroke risk in clinical trials [31]. The inverse association between sRAGE and CVD found here, which is only apparent once it has been adjusted for eGFR and other biomarkers, is contradictory and requires further exploration in other cohorts.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, it is likely that IL-6 will not add a great amount of information to a model in the presence of CRP. sRAGE has not been studied in many prospective studies of type 2 diabetes; we previously showed that higher levels were associated with an increased risk of CHD but little difference in stroke risk in clinical trials [31]. The inverse association between sRAGE and CVD found here, which is only apparent once it has been adjusted for eGFR and other biomarkers, is contradictory and requires further exploration in other cohorts.…”
Section: Discussioncontrasting
confidence: 65%
“…Remarkably, in that study RAGE levels were identical in cases and CO subjects for CV diseases. 20 However, when coronary heart disease was considered separately, sRAGE levels were higher in cases than in control subjects adjusted for age and sex. There are additional controversial results regarding sRAGE levels in atherosclerosis.…”
Section: Discussionmentioning
confidence: 95%
“…33 In the recent analysis of the CARDS study, 20 the hazard ratio for sRAGE and stroke was 0.66, but it did not reach levels of significance owing to the relatively low number (n ¼ 44) of stroke events. Remarkably, in that study RAGE levels were identical in cases and CO subjects for CV diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case-control study of middle-aged, Italian, non-diabetic men, plasma sRAGE levels were lower in men with Coronary Artery Disease (CAD) than in those without CAD, indicating the anti-inflammatory role of sRAGE. Most human studies have shown that the plasma levels of RAGE are lowers in subjects with cerebrovascular dementia, or individuals at high risk of cardiovascular disease [11][12][13][14], but contradiction data have also been reported [15][16][17][18][19]. In our previous work, CAD patients presenting with Peripheral Artery Disease (PAD) have lower sRAGE levels than CAD patients without peripheral atherosclerosis showing that stable atherosclerotic lesions in different vascular districts are inversely related to soluble levels of decoy receptor sRAGE [20].…”
Section: Discussionmentioning
confidence: 84%